Leadership Theory in Organizations - Mawardi, Mawardi; Citriadin, yudin; Azzahra, Sitti Fatimah (Pascasarjana Universitas Mataram, 2025)
This article provides some important explanations for the various definitions and theories of leadership. This research uses the library method. In this way, the authors collect data and documentation from different sources related to the topics discussed in this article. The purpose of this article is to systematically and realistically explain the facts, characteristics, and relationships between the phenomena studied. This study uses a content analysis research approach, also known as meta-analysis, specifically an analytical method that combines several types of previous research. Leadership is the process of influencing others inside and outside the organization to achieve what is desired in certain situations or conditions. It usually includes several authorities such as threats, rewards, rewards, authority, and deterrence. From a theoretical point of view, you can find different types of leadership theories: leadership traits, behaviors, and situations. Leadership Theory seeks to identify the unique physical, mental, and personal characteristics associated with successful leadership. It is based on research that combines different characteristics with certain criteria for success. Leadership theory seeks to identify the unique physical, mental, and personal characteristics associated with successful leadership.